Aerobic nitrogen cycle 100 My before permanent atmospheric oxygenation - Benjamin T. Uveges; Gareth Izon; Christopher K. Junium; Shuhei Ono; Roger E. Summons (Proceedings of the National Academy of Sciences, 2025)
The Great Oxidation Event (GOE) represents a major shift in Earth’s surficial redox balance. Delineating the driver(s) and tempo of the GOE and its impact on microbial evolution and biogeochemistry can be aided by characterizing the cycling of redox-sensitive elements such as nitrogen. While previous studies have shown that the transition to a broadly aerobic marine nitrogen cycle occurred in step with the final phase of the GOE ~2.33 billion years ago (Ga), an evolving understanding of the GOE as a dynamic oscillatory process and the narrow spatial distribution of existing studies highlight ambiguity in the marine nitrogen cycle in the lead up to permanent atmospheric oxygenation. Here, we present stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope ratios derived from the ~2.43 Ga Duitschland and ~2.33 Ga Rooihoogte formations in four drill cores separated by hundreds of kilometers. A significant negative carbon isotope excursion (6 to 8‰) in the Duitschland Formation indicates massive oxidation of organic carbon in close association with a putative snowball Earth event and an earlier pulse of atmospheric oxygen at 2.43 Ga. Further, consistently positive δ 15 N values (≤ +20.3‰) within the Duitschland Formation, combined with a broad temporal shift across global δ 15 N records to a distribution comparable to modern marine sediments, signify an aerobic nitrogen cycle ~100 My earlier than previously accepted. Our results update a key timepoint in the evolution of the marine nitrogen cycle and the oxidation of the Earth’s surface surrounding the GOE.